Tirinhas de quadrinhos: uma linguagem lúdica para a abordagem da temática socioambiental no ensino médio - BRANDÃO, Rosicleide Mota (Universidade Federal do Pará, 2022)
Our main goal was to understand how the use of comic strips in high school can arouse interest in scientific research, assisting in the education of critical students about research stages. To this end, students in the second year of high school at the João Carlos Batista State School, located in the “Quarenta Horas” neighborhood, in the city of Ananindeua-PA, Brazil, participated in a field activity around the "Quarenta Horas" River, 950m away from their school. During this activity, students observed the surroundings of the river and its condition concerning the landscape, cleanliness, silting, and surrounding community, mediated by the teacher who challenged them with questions related to habitat, diversity, ecological relations, among other contents related to environmental education. The socialization of the practice would take place in a later class; however, due to the interruption of face-to-face activity at school because of the Covid-19 pandemic, as occurred remotely, as well as the construction of comic strips elaborated by students addressing the issues raised during the field activity. The investigative activity is an action close to the student's reality, leading them to reflect, discuss, and build their knowledge consciously and actively. This activity was validated using a questionnaire called "Intrinsic Motivation Inventory (IMI1)" quantifying the student's satisfaction with the activity. From this experience, a didactic sequence was elaborated, evaluated by high school and higher education professors regarding the relevance and help for their educational practice. In the end, an experience report on the activity developed was presented, comparing it with the traditional method employed by the teacher's subject before performing this assignment.